THE PROPER OF MASHA AND THE BEAR ANIMATED SERIES AS CHILDREN’S SPECTACLE - marlina marlina (Widyariset, 2015)
Spectacle animated series is the most preferred by children. Observation of the animated series shows that some of which tend to contain negative values that can negatively impact a child's development. Generally, these negative values regarding violence, either physical or verbal violence. However, in addition to containing negative values, there is also an animated series that have educational values which can be followed by children, for example, Dora the Explorer and Upin and Ipin. Later Masha and the Bear present to enliven the spectacle of television program for children. This study aimed to assess the feasibility of the animated series Masha and the Bear as the spectacle of children. This is achieved by describing the characters of Masha and Misha the bear, as well as assessing the value of positive and negative values contained in this animated series. Description obtained by observing, listening, understanding, and parsing them one by one. The results showed that although the main character, Masha, has a naughty and mischievous character, but this  animated series worth watching for children as long as parents accompany children when watching